The Impact of Energetic Particles on the Martian Ionosphere During a Full Solar Cycle of Radar Observations: Radar Blackouts. Issue 2 (9th February 2022) - Lester, Mark; Sanchez‐Cano, Beatriz; Potts, Daniel; Lillis, Rob; Cartacci, Marco; Bernardini, Fabrizio; Orosei, Roberto; Perry, Matthew; Putzig, Nathaniel; Campbell, Bruce; Blelly, Pierre‐Louis; Milan, Steve; et al.
Abstract: We present the first long‐term characterization of ionization layers in the lower ionosphere of Mars (below ∼90 km), a region inaccessible to orbital in‐situ observations, based on an analysis of radar echo blackouts observed on Mars Express and the Mars Reconnaissance Orbiter from 2006 to 2017. A blackout occurs when the expected surface reflection is partly or totally attenuated for portions of an observation. Enhanced ionization at altitudes of 60–90 km, below the main ionospheric electron density peak, leads to increased absorption of the radar signal, resulting in the blackouts. We find that (a) MARSIS, operating at frequencies between 1.8 and 5 MHz, suffered more blackouts than SHARAD, which has a higher carrier frequency (20 MHz), (b) there is a clear correlation of blackout occurrence with solar cycle, (c) there is no apparent relationship between blackout occurrence and crustal magnetic fields, and (d) blackouts occur during both nightside and dayside observations, although the peak occurrence is deep on the nightside. Analysis of Mars Atmosphere and Volatile EvolutioN Solar Energetic Particle electron counts between 20 and 200 keV demonstrates that these electrons are likely responsible for attenuating the radar signals. We investigate the minimum SEP electron fluxes required to ionize the lower atmosphere and produce measurable attenuation. When both radars experience a blackout, the SEP electron fluxes are at their highest. Based on several case studies, we find that the average SEP spectrum responsible for a blackout is particularly enhanced at its higher energy end, that is, above 70 keV. Plain Language Summary: The orbital radars that study the surface and subsurface of Mars can suffer a near‐total loss of received signal during periods when high‐energy electrons from the Sun enter the Martian atmosphere, causing enhanced ionization at altitudes between 60 and 90 km. We have studied these radar blackouts using radars on the Mars Express and Mars Reconnaissance Orbiter spacecraft. The radars on the two spacecraft work at different frequencies, allowing us to test the theory that a larger effect is predicted at lower frequency. Indeed, we do see more blackouts of the radar operating at lower frequency (1.8–5 MHz) than at the higher frequency (20 MHz). We also find that more blackouts occur for both radars during periods of higher solar activity that is, more solar flares and Coronal Mass Ejections. The radar blackouts occur on the nightside and dayside and over all locations on the planet's surface, indicating a global effect of the solar particle events. We have also investigated the electron fluxes measured by the Mars Atmosphere and Volatile EvolutioN spacecraft and find they are higher during blackouts that include the 20 MHz frequency. These observations provide a new window on the levels of ionization at low altitudes. Key Points: First long‐term characterization of the lower ionosphere of Mars with Mars Express, Mars Reconnaissance Orbiter, and Mars Atmosphere and Volatile EvolutioN Radar sounder blackouts caused by energetic electrons occur globally at Mars Radar sounder blackouts correlate with the solar cycle